Practical Distributed Processing - Brooke, Phillip J (Undergraduate Topics in Computer Science, 2007)
At last - a comprehensive and navigable textbook on a subject of huge interest to computer professionals. Many practitioners make limited use of the advantages distributed processing theory can give them. This book show you how to design a complete distributed system.